Link-Polymorphism of 5-HTT Promoter Region Is Associated with Autoantibodies in Patients with Systemic Lupus Erythematosus - Shu Li; Shuang Liu; Fan Chen; Yuqi Cheng; Ru Bai; Aiyun Lai; Zhaoping Lu; Jian Xu (Journal of Immunology Research)
Serotonin transporter linked polymorphic region (5-HTTLPR) was reported to associate with depression in systemic lupus erythematosus (SLE) patients by our team. To explore whether 5-HTTLPR plays a role in the pathogenesis of SLE, we tested 138 SLE patients and 138 age and sex matched health controls (HCs) for 5-HTTLPR by polymerase chain reaction (PCR) and agarose gel electrophoresis. Interestingly, the results suggest that the frequencies of SS genotype and S allele in SLE patients with positive anti-Sm antibody and anti-U1RNP antibody were both significantly higher than the other genotypes and alleles. However, the frequencies of 5-HTTLPR genotypes and alleles were of no significant difference between SLE patients and HCs. This suggested that 5-HTTLPR was not a high-risk susceptible gene in SLE but might relate to SLE by affecting production of some autoantibodies, especially anti-Sm and anti-U1RNP antibody.